2017
DOI: 10.1016/j.jad.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sleep duration associated with hastened depressive recurrence in bipolar disorder

Abstract: Baseline ASD among recovered BD patients may be a risk marker for hastened depressive recurrence, suggesting it could be an important therapeutic target between mood episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The aim of this review was to summarize and discuss the recent researches on the relations between circadian rhythm dysfunction and BD (listed in Table ). Moreover, I discuss the clinical implication of circadian rhythm dysfunction on the clinical diagnosis and treatment of BD.…”
Section: Summary Of the Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this review was to summarize and discuss the recent researches on the relations between circadian rhythm dysfunction and BD (listed in Table ). Moreover, I discuss the clinical implication of circadian rhythm dysfunction on the clinical diagnosis and treatment of BD.…”
Section: Summary Of the Study Findingsmentioning
confidence: 99%
“…reported that changes in the sleep–wake cycle were likely to occur prior to mood changes during the clinical course of BD, which indicated that changes in the sleep–wake cycle may trigger relapse. A study with a 2‐year longitudinal design found that abnormal sleep duration in recovered patients may act as a risk indicator for hastened depressive recurrences . Another study reported that irregularity of a sleep–wake cycle in remitted patients could predict relapse .…”
Section: Significance Of Circadian Rhythm In the Clinical Course Of Bdmentioning
confidence: 99%
“…In bipolar disorder (BD) they may occur in 30-60% of patients, but reported rates vary from 10% to 80% depending on definition and management of potential confounding factors such as pharmacological treatments ( Steinan et al, 2016a;2016b ). Sleep disturbances have been increasingly recognized as important predictors of relapse in both major depressive disorder (MDD) and BD ( Bao et al, 2017;Bromberger et al, 2016;Craig et al, 2000;Gershon et al, 2017;Sakurai et al, 2017 ). Most descriptive studies on depressed or BD subjects with sleep alterations have focused on insomnia or decreased need to sleep, while fewer studies explored the presence of hypersomnia and its associated clinical features, despite its reported prevalence in 17-78% of patients with BD depression ( Steinan et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…Using a retrospective life chart approach, Kanady, Soehnera, and Harvey () found that manic months were associated primarily with reduced sleep need (62.8%) and insomnia (38.1%), months of predominantly depressive symptoms were characterized by hypersomnia (56.0%) and insomnia (51.9%), interepisode months were characterized primarily by insomnia (67.4%), and months of (highly dysregulated) mixed states were associated with multiple sleep problems. Hypersomnia during the euthymic phase of BD is receiving growing attention, because of its association with poor health outcomes generally and episode relapse specifically (Gershon et al, ; Kaplan, Gruber, Eidelman, Talbot, & Harvey, ): Preliminary work has identified two distinct subgroups of hypersomnia in BD—long bedrest duration and excessive sleepiness (Kaplan et al, ).…”
Section: Sleep Abnormalities In Bdmentioning
confidence: 99%
“…Research on the role of sleep disturbances has concentrated on the consequences of sleep deprivation; however, hypersomnia is also a common experience in BD (Steinan, Scott et al, ). Although less is known about the impacts of hypersomnia on BD relapses, there is emerging evidence that abnormal sleep duration is associated with next day depressive symptoms (Perlman et al, ) and hastened depressive recurrence (Gershon et al, ). This proposed relationship is also supported by evidence that hypersomnia may be a treatment target in bipolar depression: Sleep deprivation (typically combined with other chronobiological scaffolding to maintain therapeutic effects) may help ameliorate depressive symptoms in BD (Gottlieb et al, ; Suzuki et al, ).…”
Section: Predictive Role Of Sleep In Bdmentioning
confidence: 99%